2018
DOI: 10.1113/jp275166
|View full text |Cite
|
Sign up to set email alerts
|

Predictive neuromechanical simulations indicate why walking performance declines with ageing

Abstract: Key pointsr Although the natural decline in walking performance with ageing affects the quality of life of a growing elderly population, its physiological origins remain unknown.r By using predictive neuromechanical simulations of human walking with age-related neuro-musculo-skeletal changes, we find evidence that the loss of muscle strength and muscle contraction speed dominantly contribute to the reduced walking economy and speed.r The findings imply that focusing on recovering these muscular changes may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
88
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 60 publications
0
88
0
2
Order By: Relevance
“…Researchers have created controllers that could generate various gait patterns, including level walking [20-23] and running [21,23], inclined walking [22,23], loaded walking [22], stair ascent, and turning [23]. More recently, Song and colleagues sought to understand which factors contributed to decreased walking performance in the elderly population [24]. By systematically introducing the neural, muscular, or skeletal deficits seen in this population and training each model to walk, they determined that decreased muscle strength and mass of all muscles contributed…”
Section: Author Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have created controllers that could generate various gait patterns, including level walking [20-23] and running [21,23], inclined walking [22,23], loaded walking [22], stair ascent, and turning [23]. More recently, Song and colleagues sought to understand which factors contributed to decreased walking performance in the elderly population [24]. By systematically introducing the neural, muscular, or skeletal deficits seen in this population and training each model to walk, they determined that decreased muscle strength and mass of all muscles contributed…”
Section: Author Summarymentioning
confidence: 99%
“…These studies suggest strong links between muscle deficits and the observed gait adaptations; however, since these studies tracked experimental data from patients with a combination of muscular, skeletal, and neural deficits, the independent effects of muscular weakness and contracture on the observed gait adaptations cannot be assessed.Simulations in which kinematics are generated de novo (i.e., without tracking experimental data) can help reveal cause-effect relationships between muscular deficits and gait abnormalities.Researchers have created controllers that could generate various gait patterns, including level walking [20-23] and running [21,23], inclined walking [22,23], loaded walking [22], stair ascent, and turning [23]. More recently, Song and colleagues sought to understand which factors contributed to decreased walking performance in the elderly population [24]. By systematically introducing the neural, muscular, or skeletal deficits seen in this population and training each model to walk, they determined that decreased muscle strength and mass of all muscles contributed…”
mentioning
confidence: 99%
“…A larger margin of stability is viewed as safer and more stable. Recent modeling results indicate that slowed gait can be explained entirely by diminished muscle strength (Song and Geyer, 2018). However, Fan et al (2016) has shown older adults with slower gait can walk faster if instructed, suggesting that locomotor capacity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to musculoskeletal simulations, the predictive simulation approach has been more readily applied in a gait context. 17,18 Song and Geyer 18 induced neural, muscular and skeletal deficits associated with ageing to generate predictive simulations of walking in the elderly. Muscle strength and mass were subsequently identified as the predominant factors responsible for the typical gait changes seen in elderly populations.…”
mentioning
confidence: 99%
“…Muscle strength and mass were subsequently identified as the predominant factors responsible for the typical gait changes seen in elderly populations. 18 Ong et al 17 simulated isolated weakness or contracture of the plantarflexor muscles to emulate adaptations in the musculoskeletal system typically observed with cerebral palsy. Muscle weakness elucidated a slower 'heel-walking' gait, while contracture resulted in a crouched 'toewalking' gait -agreeing with the common gait adaptations seen in experimental evaluations of those with cerebral palsy.…”
mentioning
confidence: 99%